Cdk5 regulates developmental remodeling of mushroom body neurons in Drosophila. Issue 12 (14th October 2015) - Smith‐Trunova, Svetlana; Prithviraj, Ranjini; Spurrier, Joshua; Kuzina, Irina; Gu, Qun; Giniger, Edward
Abstract : Background: During metamorphosis, axons and dendrites of the mushroom body (MB) in the Drosophila central brain are remodeled extensively to support the transition from larval to adult behaviors.Results: We show here that the neuronal cyclin‐dependent kinase, Cdk5, regulates the timing and rate of mushroom body remodeling: reduced Cdk5 activity causes a delay in pruning of MB neurites, while hyperactivation accelerates it. We further show that Cdk5 cooperates with the ubiquitin‐proteasome system in this process. Finally, we show that Cdk5 modulates the first overt step in neurite disassembly, dissolution of the neuronal tubulin cytoskeleton, and provide evidence that it also acts at additional steps of MB pruning.Conclusions: These data show that Cdk5 regulates the onset and extent of remodeling of the Drosophila MB. Given the wide phylogenetic conservation of Cdk5, we suggest that it is likely to play a role in developmental remodeling in other systems, as well. Moreover, we speculate that the well‐established role of Cdk5 in neurodegeneration may involve some of the same cellular mechanisms that it uses during developmental remodeling. Developmental Dynamics 244:1550–1563, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: Cdk5/p35 kinase regulates the timing and rate of developmental remodeling of mushroom body (MB) neurons in the Drosophila brain. Cdk5/p35 acts prior to the first known step in neurite disassembly, dissolution of the microtubule cytoskeleton. Cdk5/p35 cooperates with the ubiquitin-proteasome system in MB remodeling. ex vivo pharmacological experiments provide evidence that Cdk5/p35 is apt to modulate MB pruning by a second mechanism in addition to its effects on microtubule stability.